Effects of in-situ hydrogen charging on the oxide film of iron in high-temperature water: Experiments and DFT calculations. (December 2022) - Guo, Qi; Nong, Jing; Wu, Yunlong; Liang, Fengrui; Ren, Lu; Xu, Jian; Shoji, Tetsuo
Abstract: The effects of internal hydrogen charging on the characteristics of oxide film of pure iron in high-temperature water were studied by double exposure experiments. Compared to the internally vacuumed specimen, the inner oxide film formed on the specimen with internal hydrogen charging was obviously thicker due to the sensitivity of Fe to the acceleration of oxidation by hydrogen in the matrix. The large pyramid-shaped particles in the outer layer were replaced by spherical clusters of nanocrystals after hydrogen charging. According to the DFT results, this significant difference is caused by the hindrance of hydrogen in the oxide to the adsorption and bonding process of Fe and O2 on the surface. The possible mechanism for the porous structure of oxide film caused by internal hydrogen charging is also discussed based the DFT calculations. Graph abstract: Image, graphical abstract